Essential oil compositions, pharmacological importance and agro technological practices of Patchouli (Pogostemon cablin Benth.): A review. Issue 6 (2nd November 2021) - Pandey, Sudin Kumar; Bhandari, Sangeeta; Sarma, Neelav; Begum, Twahira; Munda, Sunita; Baruah, Joyashree; Gogoi, Roktim; Haldar, Saikat; Lal, Mohan
Abstract: Patchouli ( Pogostemon cablin Benth.) is an industrially valued aromatic and important medicinal plant currently having a huge demand for its essential oil. It is widely used in flavor and fragrance industries as well as in pharmaceuticals. The essential oil is mainly isolated from the dried leaf of patchouli by steam distillation. Patchoulol and α-patchoulene are the major constituents that regulate and control patchouli essential oil quality. The major compounds of this essential oil are patchouli alcohol, α-guaiene, α-bulnesene, β-caryophyllene, α-patchoulene, γ-curcumene and some of the minor compounds are pogostone, limonene, cedrene, viridiflorol, γ-himachalene, etc. The patchouli essential oil is highly valued in perfumery and aromatherapy and is known to have various pharmacological activities such as anti-inflammatory, antiseptic, astringent, diuretic sedative, antimutagenic, antiviral, etc. Realizing the importance and industrial value of the crop, farmers are showing interest in the plantation of patchouli at a commercial scale. In this review, a broad scientific literature were looked through which incorporates Sci-hub, Pub Med, Google Scholar, Pub Chem, NIST chemistry web book and NCBI. The purpose of the review is to summarize the information's available includes Pogostemon cablin essential oil (EO) extraction and compositions, qualitative and quantitative analysis of the EOs, pharmacological importance, high essential oil yielding variety, adulteration, authentication, patchouli cultivation practices, and industrial demand of patchouli essential oil. An attempt has been made to enlighten the work of various researchers on patchouli carried out to date.